2020
DOI: 10.1038/s41598-020-79724-x
|View full text |Cite
|
Sign up to set email alerts
|

Combined lentiviral- and RNA-mediated CRISPR/Cas9 delivery for efficient and traceable gene editing in human hematopoietic stem and progenitor cells

Abstract: The CRISPR/Cas9 system is a versatile tool for functional genomics and forward genetic screens in mammalian cells. However, it has been challenging to deliver the CRISPR components to sensitive cell types, such as primary human hematopoietic stem and progenitor cells (HSPCs), partly due to lentiviral transduction of Cas9 being extremely inefficient in these cells. Here, to overcome these hurdles, we developed a combinatorial system using stable lentiviral delivery of single guide RNA (sgRNA) followed by transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…We initially planned to carry out the CRISPR-Cas9 editing of miRNAs by transducing CD34+ HSPCs with lentiviral vectors to express Cas9 and the gRNAs, followed by ex vivo erythroid differentiation. However, as reported earlier [76], we found that the transduction efficiency of CD34+ HSPCs with different Cas9 lentiviral vectors was very low. Therefore, we decided to use HUDEP-2 erythroid progenitor cells [51], which have been extensively used for experiments to study erythropoiesis using several molecular tools, including CRISPR-Cas9-based gene editing [77][78][79].…”
Section: Crispr-cas9-mediated Gene Editing Of Mirnassupporting
confidence: 82%
“…We initially planned to carry out the CRISPR-Cas9 editing of miRNAs by transducing CD34+ HSPCs with lentiviral vectors to express Cas9 and the gRNAs, followed by ex vivo erythroid differentiation. However, as reported earlier [76], we found that the transduction efficiency of CD34+ HSPCs with different Cas9 lentiviral vectors was very low. Therefore, we decided to use HUDEP-2 erythroid progenitor cells [51], which have been extensively used for experiments to study erythropoiesis using several molecular tools, including CRISPR-Cas9-based gene editing [77][78][79].…”
Section: Crispr-cas9-mediated Gene Editing Of Mirnassupporting
confidence: 82%
“…Here, we set out to explore different strategies to simultaneously knockout two genes using our recently published split CRISPR/Cas9 delivery system in cord blood (CB)-derived CD34 + HSPCs 14 . In our previous work, using a chimeric sgRNA backbone, we identified highly efficient sgRNAs targeting the two cell surface markers CD45 and CD44.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported on a split CRISPR/Cas9 delivery system, combining stable lentiviral sgRNA delivery and transient delivery of Cas9 mRNA, for efficient and traceable gene editing in primary CD34 + HSPCs 14 . The use of lentiviral sgRNA vectors containing fluorescent markers allows extension of this system to traceable multiplexed perturbations 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Scientists can easily search for a particular gene on specific websites and select from a range of available vectors. In particular, the use of the lentivirus as a means of delivering DNA to transfection-resistant cells is an effective method for producing stable Cas9 and sgRNA cell lines [ 18 ].…”
Section: Reagents In Crispr/casmentioning
confidence: 99%